1991
DOI: 10.1126/science.1833820
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Growth of Virulent Strains of Escherichia coli by Interleukin-1

Abstract: Interleukin-1 (IL-1) is a polypeptide cytokine that mediates many physiological responses to infection and inflammation and is a growth factor for certain mammalian cells. Virulent and avirulent clinical isolates of Escherichia coli were grown in culture media in the presence of human IL-1. IL-1 beta, but not tumor necrosis factor or IL-4, enhanced the growth of virulent, but not avirulent, E. coli. This enhancement was blocked by the IL-1 receptor antagonist (IL-1ra). Radiolabeled IL-1 bound to virulent but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
121
0
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(127 citation statements)
references
References 21 publications
5
121
0
1
Order By: Relevance
“…3a and b show the results of SDS-PAGE and immunoblot analyses, respectively, of the bound and subsequently eluted protein complex. It can be seen from It has been reported that some Gram-negative bacteria produce a protein with IL-l-like activities [16]. We found that in a search of the PIR protein sequence library, Cafl shared the highest level of homology with hIL-lra (28% identity between aa 62 89 of Cafl and aa 57-85 of hIL-lra) [15].…”
Section: Competition Between Cafl and Hll-l~ For Binding To Caflamentioning
confidence: 66%
See 1 more Smart Citation
“…3a and b show the results of SDS-PAGE and immunoblot analyses, respectively, of the bound and subsequently eluted protein complex. It can be seen from It has been reported that some Gram-negative bacteria produce a protein with IL-l-like activities [16]. We found that in a search of the PIR protein sequence library, Cafl shared the highest level of homology with hIL-lra (28% identity between aa 62 89 of Cafl and aa 57-85 of hIL-lra) [15].…”
Section: Competition Between Cafl and Hll-l~ For Binding To Caflamentioning
confidence: 66%
“…Each of these operons encode an outer membrane usher protein which facilitates surface localisation and correct assembly of virulence-associated surface organelles (capsules, pili, fimbriae). Porat et al [16] have found that IL-1 displays reactivity with virulent E. coli strains and increases the number of colony-forming entities. It was proposed that human IL-1 may recognize a functional IL-l-like receptor structure on virulent E. coli and may be a virulence factor for bacterial pathogenicity.…”
Section: Identification Of Cafla As Hll-l[~ Receptormentioning
confidence: 99%
“…Findings that relate to the ability of AAT to inhibit bacterial expansion include binding to the bacterialessential furin (135), as well as undergoing S-nitrosylation in the presence of nitric oxide (136), both actions that are independent of protease inhibition. The observation that the virulence of E. coli is increased by IL-1 (137) suggests that blockade of IL-1 by AAT may interfere with bacterial growth, a finding corroborated by reduced numbers of live S. pneumoniae in infected mouse lungs (EC Lewis, unpublished observations). In this context, notably, the role of AAT in reducing bacterial load involves tissue modulation, that is, reducing the levels of tissue-derived bioactive IL-1.…”
Section: Aat Is An Antibacterialmentioning
confidence: 83%
“…The authors proposed that monocytes in CD14-deficient mice were not activated by bacteria due to lack of mCD14, and this in turn reduced production of inflammatory cytokines, such as TNF-a and IL-1, which accelerate growth of bacteria [25,32]. The authors postulated that reagents capable of blocking or neutralizing mCD14 on monocytes might also inhibit growth of Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%